Medicine meets virtual reality 14: accelerating change in healthcare : next medical toolkit - Westwood, James D. (Studies in health technology and informatics, 2006)
The remarkable accomplishments of the IT industry and the Internet are trickling steadily into healthcare. This series provides more effective healthcare at a lower overall cost, driven by cheaper and better computers